Efektivitas Penggunaan Hafiz Doll terhadap Hafalan Doa Pendek pada Anak Usia 1-3 Tahun - Rista Erika; Muhammad Rizal Zaenulloh; Mia Siti Nurazizah; Eva Manfaatin; Samsu Nurfalah (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study aims to describe the use of the Hafiz Doll as a supporting medium for introducing the memorization of short prayers to children aged 1–3 years within the family environment. The research employed a descriptive qualitative approach, involving one child aged 2.5 years with parents serving as the primary facilitators. The findings indicate that the use of the Hafiz Doll elicited initial child responses, including more focused attention, positive emotional engagement, and simple verbal repetition of prayer sounds. These results suggest that doll-based media incorporating audio and visual stimulation can function as a supportive tool for habituating prayer practices at the early stages of child development. The contribution of this study lies in providing an empirical portrayal of the use of interactive religious media in the context of spiritual learning for children aged 1–3 years in the home setting, with particular emphasis on the role of parental guidance and the contextual limitations of the study.